Aphandra natalia(Arecaceae) – a little known source of piassaba fibers from the western Amazon - Kronborg, Mette (2008)
Aphandra natalia(Balslev & Henderson) Barfod is a multipurpose palm that is exploited both commercially and for subsistence purposes. Its fibers are important in Peruvian and Ecuadorean broom industries and support many people economically. In Brazil, it is found in the western part of Acre, where it is the main source for a local broom market. Data from fieldwork in Peru (2007) suggests that the variation in gross profit per kilogram of fiber is considerable among the different segments in the broom industry. Harvesters and distributors earn negligible amounts of money whereas manufacturers reap of the major part of the earnings. Fiber extraction appears to be sustainable in Ecuador and in some parts of Peru, whereas in other parts of Peru unsustainable harvest occurs, involving felling of entire palm trees for the harvest of fibers. The same destructive extraction method is used in Brazil, where the palm is becoming rare in its natural distribution area.